Oral repercussions in patients undergoing hematopoietic stem cell transplantations: An integrative review of the literature (Research, Society and Development, 2023)
Aim: This integrative review aimed to identify and describe oral changes resulting from HSCT, as well as evaluate the importance of dental care in the face of these complications. Methodology: An integrative literature review was carried out with bibliographic research of scientific articles in the electronic databases PubMed, Scielo and Biblioteca Virtual em Saúde (BVS) between the years 2009 and 2023. The following descriptors were used for the search: “hematopoietic stem cell transplantation”, “oral manifestations”, “mucositis”, “xerostomia” “dental care”, “dysgeusia”. Results: The main manifestations found were: oral mucositis, xerostomia, ulcerations, erythema, Graft Versus Host Disease (GVHD) and lichenoid lesions. Conclusion: Most patients undergoing HSCT have oral repercussions from the conditioning period to post-HSCT and such conditions affect the quality of life and survival of these patients, contributing to increased length of hospital stay. Therefore, the presence of a qualified dental surgeon at hospitals becomes necessary in the multidisciplinary team, in order to contribute to a significant increase in the patients’ quality of life.